Newborn Screening Saves Lives but Cannot Replace the Need for Clinical Vigilance - F. Neemuchwala; M. Taki; E. Secord; S. Z. Nasr (Hindawi Limited, 2018)
Newborn screening for cystic fibrosis (CF) enables early diagnosis and treatment leading to improved health outcomes for patients with CF. Although the sensitivity of newborn screening is high, false-negative results can still occur which can be misleading if clinicians are not aware of the clinical presentation of CF. We present a case of a young male with negative newborn screen diagnosed for CF. He was diagnosed at 3 years of age despite having symptoms indicative of CF since infancy. The delayed diagnosis resulted in diffuse lung damage and poor growth.